2013
DOI: 10.1371/journal.pone.0079455
|View full text |Cite
|
Sign up to set email alerts
|

Copper Promotes TFF1-Mediated Helicobacter pylori Colonization

Abstract: The trefoil peptides (TFF1, TFF2 and TFF3) are a family of small highly conserved proteins that play an essential role in epithelial regeneration within the gastrointestinal tract, where they are mainly expressed. TFF1 expression is strongly induced after mucosal injury and it has been proposed that tff1 functions as a gastric tumor suppressor gene. Several studies confirm that tff1 expression is frequently lost in gastric cancer because of deletions, mutations or methylation of the tff1 promoter. Infection by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…H. pylori is also capable of interacting with TFF3 dimer at >pH 7.0, but not with TFF2; even glycosylated TFF2 was shown not to interact with H. pylori (63, 125). The C-terminal of TFF1 can also specifically bind copper ions, which enhances H. pylori binding to TFF1 (126). However, MUC5AC is downregulated late in the gastric epithelium after H. pylori infection or ulceration (112, 127).…”
Section: Trefoil Factor and Gastrointestinal Diseasesmentioning
confidence: 99%
“…H. pylori is also capable of interacting with TFF3 dimer at >pH 7.0, but not with TFF2; even glycosylated TFF2 was shown not to interact with H. pylori (63, 125). The C-terminal of TFF1 can also specifically bind copper ions, which enhances H. pylori binding to TFF1 (126). However, MUC5AC is downregulated late in the gastric epithelium after H. pylori infection or ulceration (112, 127).…”
Section: Trefoil Factor and Gastrointestinal Diseasesmentioning
confidence: 99%
“…Copper-mediated colonization of the stomach mucosa occurs through the action of trefoil peptides in H. pylori (Montefusco et al 2013) and copper drastically increases in cancerous tissues. However the detailed role of copA and copP genes and of copper metabolism in H. pylori long-term adaptation is yet to be investigated.…”
Section: Genes Involved In Heavy Metal Metabolismmentioning
confidence: 99%
“…Hence, the consequence of lost Piezo1 is sophisticated and depends on the origin of the tumour tissues. Montefusco et al [119] have reported that copper ions (Cu) promotes TFF1-mediated Hp colonization and Cu binding favours the homodimerization of TFF1 (Table 2), thus reinforcing its motogenic activity.…”
Section: Accepted Manuscriptmentioning
confidence: 99%